Accountability and public trust in local government services / Nor Zaini Zainal Abidin - Nor Zaini , Zainal Abidin (2018)
The premise of this research is that people would trust government in a normal situation unless they encountered an unexpected experienced with government officials especially in service delivery. Alas, public servants are accountable of their actions and as the provider of public service; they must carry out the services in an effective and ethical manner. According to Principal-Agent Theory, the interaction between the principal and an agent happens when the principal delegates the task to an agent. Thus, in public service, the government as the principal entrusts the public servants to carry out the duties in serving the public. Additionally, social capital theory confirms that the interaction and cooperation between individuals depend on the level of social capital in a society. The ease of relationship is based on networks, norms and trust. Social Capital Theory explains the existence of ethics in the conduct of the behavior of public servants. In this sense, ethical accountability plays an important part in securing public trust. Thus, three objectives has been identified: (1) to determine the level of accountability and ethical accountability in the role of local government in the provision of local government services, (3) to investigate the relationship between public trust, accountability and ethical accountability in the provision of local government services, and, (3) to examine the scope and ability of local government in the provision of local government services. Applying Principal-Agent Theory and complemented by Social Capital Theory, this research attempts to investigate accountability and ethical accountability in the provision of local government services in Kuala Lumpur and Selangor local authorities. Although much has been done to investigate various outcomes of local government service delivery, not much has been done to relate accountability, ethical accountability and public trust in local government. Further, none has been done about the influence of loyalty as mediator to public trust. Furthermore, this research incorporates social capital as public goods that can be acquired and nurtured to gain public trust. A cross-sectional survey was chosen to collect data from 608 respondents from the only local authority in Kuala Lumpur and those in Selangor. A partial least squares technique was applied to examine the direct and indirect effects between key variables. Six mediator variables were tested by using Preacher and Hayes technique using PLS. Result shows that most of mediator variables were supported with loyalty as newly introduced mediator also has a significant relationship to public trust. However, the findings showed that benevolence as a mediator variable is not supported. Findings confirmed that the existence of ethical accountability can make public to trust government better. This research makes several theoretical contributions and provides further insight on accountability, ethical accountability and public trust in the provision of local government services. Methodological and practical implications are discussed and several potential avenues for future research have been identified and proposed. In short, this research helped to identify important variables of ethical accountability as mediator to public trust.